Derivasi atau Arketipe: Mengusut The Logical Structure of Islamic Theology Karya Josef Van Ess - Lubis, Ali Akhbar Abaib Mas Rabbani; Muzakki, Muhammad Harir (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
The focus of this paper is on Josef Van Ess's The Logical Structure of Islamic Theology. An important argument regarding the thought of kalam is that it fully involves the relationship of revelation, reason, and human experience. This writing aims to answer the question whether the discipline of kalam in its logical structure is derived from Greco-Roman or archetypes from the Islamic tradition? This writing includes a qualitative research cluster involving library research, then the ma'na-cum-maghza approach through the stages of data reduction, data exposure, and drawing conclusions or verification. The result of the conclusion is that Ess's opinion always changes and improves the statement regarding the nominalistic term kalam, although according to Ess it is not impossible that the science of kalam and its spectrum such as Islamic Law technically reflects Greco-Roman rhetoric and is preserved in Islamic Tradition.